Self-management, care needs and clinical management of primiparous mothers during early labour - a qualitative content analysis - Antonia N. Mueller; Susanne Grylka-Baeschlin (BMC, 2023)
Abstract Background Childbearing women face the problem of managing spontaneous onset of labour without professional support. It is their responsibility to diagnose and react to early labour and subsequently recognise the right time to seek support. Institutional guidelines of clinics aim to admit childbearing women when in established labour. This explains why women in early labour are often advised to stay at home, which can be overwhelming and dissatisfying. This study aims to understand the self- and clinical management of early labour and care needs of first-time mothers during early labour. Methods A qualitative approach was used involving four focus group discussions with a total of N = 18 mothers. Included were primiparous women who had given birth at term within the last 6 months and who experienced spontaneous onset of labour. Elective caesarean section or induction of labour were thereby exclusion criteria. The interviews followed a semi-structured, literature-based guide. Content analysis was applied. Results Thirteen codes were summarised within three themes: 'self-management', 'care needs' and 'professional management'. Various coping strategies and measures such as positive thinking or taking a bath helped women in managing early labour at home. The need for reassurance, professional guidance and pain management led them to seek professional support, which was initially accompanied by a feeling of inhibition. This negative emotion was mostly unjustified since many women felt well cared for and taken seriously in their needs. Conclusion Coping strategies and professional care help women going through early labour. Yet, there still exists insecurity about the justified timing in seeking professional support. An individual assessment of the women's coping resources and their needs is required to promote shared decision making and give high-standard care.